Belief Echoes: The Persistent Effects of Corrected Misinformation. (2nd July 2016) - Thorson, Emily
Abstract : Across three separate experiments, I find that exposure to negative political information continues to shape attitudes even after the information has been effectively discredited. I call these effects "belief echoes." Results suggest that belief echoes can be created through an automatic or deliberative process. Belief echoes occur even when the misinformation is corrected immediately, the "gold standard" of journalistic fact-checking. The existence of belief echoes raises ethical concerns about journalists' and fact-checking organizations' efforts to publicly correct false claims.